Enhancement of Sports Nutrition Knowledge and Energy Intake after Sports Nutrition Education for Combat Athletes - Pratiwi, Rachmahnia; Siti Rahayu Nadhiroh (Media Gizi Indonesia, 2024)
Providing nutrition and food support is necessary for enhancing and maximizing athletic performance in individuals engaged in sports activities. This study aimed to examine the impact of sports nutrition education on combat athletes' sports nutrition knowledge and nutritional sufficiency. This quantitative study used a quasi-experimental design, explicitly utilizing a pretest-posttest control group design. The study included a total of 76 participants, who were categorized into two groups: intervention and control. Each group consisted of 38 athletes. The data were analysed using SPSS. The Independent T-Test and Paired T-Test determined if the data followed a normal distribution. The Mann-Whitney and Wilcoxon Signed Rank tests were employed if the data did  not follow a normal distribution. The nutrition education intervention comprised seven weekly materials sent to the intervention group. The findings indicated significant nutritional knowledge differences (p=<0.001) between the intervention and control groups. Additionally, there were significant differences in the sufficiency of energy intake (p=0.029) within the intervention group. The study's findings indicated that nutrition education significantly affected the intervention group's sports nutrition knowledge and energy intake adequacy. Additionally, the nutrition education intervention significantly affected the sports nutrition knowledge of the control group. Athletes' enhanced understanding will positively affect their ability to satisfy energy requirements.